Insulating resin composition, cured insulating resin body, laminate and circuit board
The insulating resin composition addresses the challenges of high voltage circuit boards by forming a layer with balanced adhesivity and insulation, enhancing thermal conductivity and moisture resistance, suitable for automotive applications.
Patent Information
- Application Number
- JP2021554851
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-08
- Filing Date
- 2020-10-07
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2040-10-07
AI Technical Summary
Conventional circuit boards used in fast chargers for automobiles face challenges with high voltage applications, requiring improved moisture-resistant adhesion, insulation, and thermal conductivity, while maintaining adhesion strength under high temperature and humidity conditions.
An insulating resin composition containing organic materials like epoxy resin, curing agents, phosphate compounds, and inorganic fillers, along with heavy metal inactivation agents and hindered phenol antioxidants, is used to form an insulating layer with balanced adhesivity, insulation, and low elasticity, enhancing thermal conductivity and moisture resistance.
The insulating resin composition forms a layer that maintains excellent adhesivity and insulation in high-temperature and humidity environments, providing a circuit substrate with improved thermal conductivity, moisture resistance, and heat resistance.
Smart Images

Figure 0007625530000007 
Figure 0007625530000008 
Figure 0007625530000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an insulating resin composition suitable for use in the manufacture of a metal base circuit board and a cured product thereof. The present invention also relates to a laminate and a circuit board formed using the insulating resin composition. [Background technology]
[0002] A variety of circuit boards have been put to practical use as circuit boards on which electronic and electrical components such as semiconductor elements are mounted to form hybrid integrated circuits. Circuit boards are classified based on the board material into resin circuit boards, ceramic circuit boards, metal-based circuit boards, etc.
[0003] Resin circuit boards are inexpensive, but because the thermal conductivity of the board is low, their use is limited to applications requiring relatively low power. Ceramic circuit boards, which feature ceramics with their high electrical insulation and heat resistance, are suitable for applications requiring relatively high power, but have the disadvantage of being expensive. On the other hand, metal-based circuit boards have intermediate properties between the two and are suitable for general-purpose applications requiring relatively high power, such as power sources for refrigerators, home air conditioners, automobiles, and high-speed trains.
[0004] For example, Patent Document 1 discloses a method for obtaining a circuit board having excellent stress relaxation properties, heat resistance, moisture resistance, and heat dissipation properties by using a composition for circuit boards containing a specific epoxy resin, a curing agent, and an inorganic filler as essential components. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-266535 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, the demand for automobile quick chargers has increased due to the spread of plug-in hybrid vehicles, electric vehicles, etc. Circuit boards used for such chargers are used at higher voltages than conventional automobile circuit boards, and therefore are required to have higher moisture-resistant adhesion and moisture-resistant insulation, as well as thermal conductivity and heat cycle resistance equal to or greater than those of conventional automobile circuit boards.
[0007] One method for improving the heat cycle resistance of a circuit board is to reduce the elastic modulus of the insulating layer to relieve thermal stress and thereby suppress the progression of solder cracks. However, when the elastic modulus of the insulating layer is reduced, the adhesive strength between the metal foil and the insulating layer is likely to decrease under conditions of high temperature and high humidity and application of DC voltage, which may cause the metal foil to bulge.
[0008] The present invention aims to provide an insulating resin composition capable of forming an insulating layer that has excellent adhesion and insulating properties and a low elastic modulus in a high-temperature and high-humidity environment, and a cured product thereof. Another object of the present invention is to provide a circuit board that has an insulating layer made of a cured product of the insulating resin composition and has excellent moisture-resistant insulation, thermal conductivity, and heat cycle resistance. [Means for solving the problem]
[0009] One aspect of the present invention relates to an insulating resin composition containing an organic material and an inorganic filler, wherein the organic material contains an epoxy resin, a curing agent, a phosphate compound having one or more hydroxyl groups in one molecule, a heavy metal deactivator, and a hindered phenol-based antioxidant, and the content of the inorganic filler is 50% by mass or more and 95% by mass or less.
[0010] In one embodiment, the curing agent may be an amine-based curing agent.
[0011] In one embodiment, the amine curing agent may contain a first amine curing agent having an amine equivalent of 300 or less and a second amine curing agent having an amine equivalent of 800 or more.
[0012] In one embodiment, the content of the heavy metal deactivator may be 0.01 to 0.5% by mass based on the total amount of the organic material and the inorganic filler.
[0013] In one embodiment, the content of the hindered phenol-based antioxidant may be 0.05 to 5 mass % based on the total amount of the organic material.
[0014] In one embodiment, the content of the phosphate ester compound may be 0.05 to 0.4 mass % based on the total amount of the organic material and the inorganic filler.
[0015] In one embodiment, the melting point of the heavy metal deactivator may be 250° C. or less.
[0016] Another aspect of the present invention relates to an insulating resin cured product, which is a cured product of the insulating resin composition.
[0017] The insulating resin cured body according to one embodiment may have a storage modulus at 85° C. of 500 MPa or less.
[0018] Yet another aspect of the present invention relates to a laminate including a metal plate, the cured insulating resin body disposed on the metal plate, and a metal foil disposed on the cured insulating resin body.
[0019] Yet another aspect of the present invention relates to a circuit board including a metal plate, the cured insulating resin body disposed on the metal plate, and a circuit portion disposed on the cured insulating resin body. Effect of the Invention
[0020] According to the present invention, there is provided an insulating resin composition capable of forming an insulating layer having excellent adhesion and insulating properties in a high-temperature and high-humidity environment and a low elastic modulus, and a cured product thereof. Also, according to the present invention, there is provided a circuit board having an insulating layer made of the cured product of the insulating resin composition, and having excellent moisture-resistant insulation, thermal conductivity, and heat cycle resistance. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a laminate. [Diagram 2] FIG. 2 is a cross-sectional view illustrating an embodiment of a circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Preferred embodiments of the present invention will now be described in detail.
[0023] (Insulating resin composition) The insulating resin composition of the present embodiment contains an organic material and an inorganic filler, and the content of the inorganic filler is 50% by mass or more and 95% by mass or less. The insulating resin composition of the present embodiment contains, as organic materials, an epoxy resin, a curing agent, a phosphoric acid ester compound having one or more hydroxyl groups in one molecule, a heavy metal deactivator, and a hindered phenol-based antioxidant.
[0024] The insulating resin composition can form a cured product (insulating layer) that has excellent adhesiveness and insulating properties in a high-temperature and high-humidity environment and a low elastic modulus. Therefore, the insulating resin composition can be suitably used to form an insulating layer for a circuit board (particularly a metal-based circuit board). The reason why the present embodiment exhibits the above-mentioned effects is not necessarily clear, but is thought to be as follows.
[0025] In this embodiment, the phosphate ester compound is believed to improve the dispersibility and adhesion between the resin component and the inorganic filler due to the presence of hydroxyl groups in the molecule, thereby improving the moisture-resistant adhesion. In addition, the phosphate ester compound is believed to suppress the decrease in moisture-resistant insulation caused by the oxidative deterioration of the insulating layer by trapping OH radicals generated under conditions of high temperature and high humidity and application of DC voltage.
[0026] Furthermore, in this embodiment, it is believed that the hindered phenol-based antioxidant further plays a role in trapping radicals, and through interaction with the phosphate ester compound, the oxidative deterioration of the insulating layer is more significantly suppressed, and the moisture-resistant insulating properties are further improved.
[0027] In addition, the migration of ionic impurities into the insulating layer is considered to be a cause of the deterioration of adhesion and insulation, but in this embodiment, the heavy metal deactivator captures the metal ions, and it is considered that the adverse effects of migration are suppressed. In particular, when a metal plate such as a metal base circuit board and an insulating layer are adjacent to each other, metal ions (e.g., copper ions) may be eluted from the metal plate to the insulating layer, but according to the insulating resin composition of this embodiment, an insulating layer that can maintain excellent moisture-resistant adhesion and moisture-resistant insulation can be formed even when adjacent to a metal plate.
[0028] In the present embodiment, it is believed that a cross-linked structure is formed in the cured body by the epoxy resin and the amine-based curing agent, thereby making it possible to reduce the elastic modulus of the cured body while significantly obtaining the effects of the above-mentioned phosphate ester compound, hindered phenol-based antioxidant, and heavy metal deactivator.
[0029] The epoxy resin may be any epoxy resin that is cured by an amine-based curing agent to exhibit an adhesive effect. Examples of the epoxy resin include bifunctional epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol A / F type epoxy resin; novolac type epoxy resins such as phenol novolac type epoxy resin and cresol novolac type epoxy resin; multifunctional epoxy resins such as trisphenol methane type epoxy resin; glycidyl amine type epoxy resin; heterocyclic epoxy resins such as triglycidyl isocyanurate, and alicyclic epoxy resins such as hydrogenated bisphenol A type epoxy resin and hydrogenated bisphenol F type epoxy resin.
[0030] As the epoxy resin, among the above, a bifunctional epoxy resin (bifunctional aromatic epoxy resin) and an alicyclic epoxy resin can be suitably used. By using these epoxy resins, the heat cycle resistance of the circuit board tends to be further improved. The insulating resin composition according to the present embodiment may contain at least one of a bifunctional epoxy resin and an alicyclic epoxy resin, or may contain both a bifunctional epoxy resin and an alicyclic epoxy resin.
[0031] When the insulating resin composition contains a difunctional epoxy resin and an alicyclic epoxy resin, the content A of the difunctional epoxy resin 1 A content of alicyclic epoxy resin 2 Ratio of (A 2 / A 1 The ratio (A, mass ratio) may be, for example, 1.5 or more, preferably 2.0 or more, and more preferably 2.5 or more. This tends to further improve the heat cycle resistance of the circuit board. 2 / A 1 The ratio (A, mass ratio) may be, for example, 8.0 or less, preferably 6.0 or less, and more preferably 4.0 or less. This tends to further improve the insulating properties and adhesiveness of the cured body. 2 / A 1 , mass ratio) may be, for example, 1.5 to 8.0, 1.5 to 6.0, 1.5 to 4.0, 2.0 to 8.0, 2.0 to 6.0, 2.0 to 4.0, 2.5 to 8.0, 2.5 to 6.0, or 2.5 to 4.0.
[0032] The content of the epoxy resin in the insulating resin composition may be, for example, 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more, based on the total amount of the organic material. The content of the epoxy resin may be, for example, 90% by mass or less, preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, based on the total amount of the organic material. That is, the content of the epoxy resin in the insulating resin composition may be, for example, 50 to 90 mass%, 50 to 85 mass%, 50 to 80 mass%, 50 to 75 mass%, 55 to 90 mass%, 55 to 85 mass%, 55 to 80 mass%, 55 to 75 mass%, 60 to 90 mass%, 60 to 85 mass%, 60 to 80 mass%, 60 to 75 mass%, 65 to 90 mass%, 65 to 85 mass%, 65 to 80 mass%, or 65 to 75 mass%, based on the total amount of the organic material.
[0033] The curing agent may be any curing agent capable of curing an epoxy resin. Examples of the curing agent include amine-based curing agents, phenol-based curing agents, and acid anhydride-based curing agents. Among these, amine-based curing agents are preferred from the viewpoint of further improving moisture-resistant adhesion and moisture-resistant insulation.
[0034] The amine-based curing agent may be any curing agent that has an amino group and is capable of curing an epoxy resin. Examples of the amine-based curing agent include aromatic amine-based curing agents, aliphatic amine-based curing agents, and dicyandiamide.
[0035] As the amine-based curing agent, an aliphatic amine-based curing agent is preferred from the viewpoint of further improving the heat cycle resistance of the circuit board.
[0036] The amine curing agent preferably contains a first amine curing agent having an amine equivalent of 300 or less and a second amine curing agent having an amine equivalent of 800 or more. By using two types of amine curing agents with different amine equivalents in combination, the crosslinked structure of the epoxy resin becomes coarse and dense during curing, and the elastic modulus of the cured body tends to be further reduced.
[0037] The amine-based curing agent preferably contains an amine-based curing agent having a polyether chain, more preferably at least one of the first amine-based curing agent and the second amine-based curing agent has a polyether chain, and even more preferably both the first amine-based curing agent and the second amine-based curing agent have a polyether chain. Since the amine-based curing agent having a polyether chain has excellent compatibility with epoxy resins, by using such an amine-based curing agent, it becomes easier to obtain a cured product having even better adhesion and heat resistance. The polyether chain is preferably a polyoxyalkylene chain, more preferably a polyoxyalkylene chain having an alkylene group selected from the group consisting of an ethylene group and a propylene group.
[0038] Both the first amine-based curing agent and the second amine-based curing agent are preferably aliphatic amine-based curing agents.
[0039] It is preferable that each of the first amine-based curing agent and the second amine-based curing agent is a curing agent having two amino groups in one molecule.
[0040] Content B of the first amine-based curing agent in the insulating resin composition 1 Content of second amine-based hardener B 2 Ratio (B 2 / B 1 , mass ratio) may be, for example, 0.2 or more, preferably 0.25 or more, and more preferably 0.3 or more. This tends to further improve the heat cycle resistance of the circuit board. 2 / B 1 , mass ratio) may be, for example, 2.0 or less, preferably 1.5 or less, and more preferably 1.0 or less. This tends to further improve the insulating properties, adhesive properties, and heat resistance of the cured product. That is, the above ratio (B 2 / B 1 , mass ratio) may be, for example, 0.2 to 2.0, 0.2 to 1.5, 0.2 to 1.0, 0.25 to 2.0, 0.25 to 1.5, 0.25 to 1.0, 0.3 to 2.0, 0.3 to 1.5, or 0.3 to 1.0.
[0041] The amount of hardener added depends on the epoxy equivalent (C 1 ) to the active hydrogen equivalent (or acid anhydride equivalent) of the curing agent (C 2 ) ratio (C 2 / C 1 ) may be determined based on the ratio (C 2 / C 1 ) is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more. 2 / C 1 ) is preferably 2.5 or less, more preferably 2.0 or less, and even more preferably 1.5 or less. That is, the ratio (C 2 / C 1 ) may be, for example, 0.1 to 2.5, 0.1 to 2.0, 0.1 to 1.5, 0.2 to 2.5, 0.2 to 2.0, 0.2 to 1.5, 0.3 to 2.5, 0.3 to 2.0, or 0.3 to 1.5.
[0042] The phosphoric acid ester compound has one or more hydroxyl groups in one molecule. In this embodiment, the phosphoric acid ester compound is considered to have the effect of improving the dispersibility and adhesion between the resin component and the inorganic filler and improving the moisture-resistant adhesion due to the presence of hydroxyl groups in the molecule. In addition, the above phosphoric acid ester compound is considered to have the effect of suppressing the decrease in moisture-resistant insulation caused by the oxidative deterioration of the insulating layer by trapping OH radicals generated under conditions of high temperature and high humidity environment and application of DC voltage.
[0043] The number of hydroxyl groups that the phosphate ester compound has is more preferably 1 to 2 per molecule, and even more preferably 2 per molecule.
[0044] The phosphate ester compound preferably has a hydroxyl group directly bonded to the phosphorus atom, and more preferably has two hydroxyl groups directly bonded to the phosphorus atom.
[0045] The phosphate ester compound preferably contains a polyether chain from the viewpoints of excellent compatibility with the epoxy resin and the curing agent, and further improving adhesion between the inorganic filler and the resin component. The polyether chain is preferably a polyoxyalkylene chain, and more preferably a polyoxyalkylene chain having an alkylene group selected from the group consisting of an ethylene group and a propylene group.
[0046] The phosphate compound preferably contains an oxycarbonyl group from the viewpoints of excellent compatibility with the epoxy resin and the curing agent, and further improving adhesion between the inorganic filler and the resin component.
[0047] The number average molecular weight of the phosphate ester compound is preferably 200 or more, and more preferably 400 or more. The number average molecular weight of the phosphate ester compound is preferably 2000 or less, and more preferably 1000 or less. The number average molecular weight of the phosphate ester compound is a value measured by size exclusion chromatography (GPC). That is, the number average molecular weight of the phosphate ester compound may be, for example, 200 to 2000, 200 to 1000, 400 to 2000, or 400 to 1000.
[0048] The phosphate compound may be, for example, a compound represented by the following formula (1).
[0049] [ka]
[0050] In formula (1), R represents a monovalent group having a polyether chain. R may further have a polyester chain.
[0051] The content of the phosphoric acid ester compound in the insulating resin composition may be, for example, 0.05% by mass or more, preferably 0.1% by mass or more, based on the total amount of the organic material and the inorganic filler. This makes the above-mentioned effect of the phosphoric acid ester compound more pronounced. The content of the phosphoric acid ester compound in the insulating resin composition may be, for example, 0.4% by mass or less, preferably 0.3% by mass or less, based on the total amount of the organic material and the inorganic filler. This suppresses the decrease in moisture-resistant insulation and moisture-resistant adhesion caused by moisture absorption and hydrolysis of the phosphoric acid ester compound itself, and tends to further improve the heat cycle resistance of the circuit member. That is, the content of the phosphoric acid ester compound in the insulating resin composition may be, for example, 0.05 to 0.4% by mass, 0.05 to 0.3% by mass, 0.1 to 0.4% by mass, or 0.1 to 0.3% by mass, based on the total amount of the organic material and the inorganic filler.
[0052] The heavy metal deactivator may be, for example, one that can capture metal ions (such as copper ions) by chelating them in the insulating resin composition or a cured product thereof.
[0053] As the heavy metal deactivator, for example, nitrogen-containing deactivators such as hydrazine-based heavy metal deactivators and triazole-based heavy metal deactivators can be suitably used.
[0054] Examples of heavy metal deactivators include dodecanedioic acid bis[N2-(2-hydroxybenzoyl)hydrazide] (product name "CDA-6", manufactured by ADEKA), N-(2H-1,2,4-triazol-5-yl)salicylamide (product name "CDA-1", manufactured by ADEKA), N,N'-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}hydrazine (product name "CDA-10", manufactured by ADEKA), and 3-amino-1,2,4-triazole.
[0055] From the viewpoint of further improving dispersibility in the insulating resin composition, the heavy metal deactivator preferably has a low melting point. The melting point of the heavy metal deactivator may be, for example, 250° C. or lower, preferably 240° C. or lower, more preferably 230° C. or lower, and even more preferably 220° C. or lower.
[0056] The content of the heavy metal deactivator in the insulating resin composition may be, for example, 0.01% by mass or more, preferably 0.03% by mass or more, more preferably 0.05% by mass or more, based on the total amount of the organic material and the inorganic filler. This makes the above-mentioned effect of the heavy metal deactivator more pronounced, and tends to further improve the moisture-resistant adhesion. In addition, the content of the heavy metal deactivator in the insulating resin composition may be, for example, 0.5% by mass or less, preferably 0.3% by mass or less, more preferably 0.2% by mass or less, based on the total amount of the organic material and the inorganic filler. This further improves the coatability of the insulating resin composition, and tends to further improve the moisture-resistant insulation and reliability of the circuit board. That is, the content of the heavy metal deactivator in the insulating resin composition may be, for example, 0.01 to 0.5 mass%, 0.01 to 0.3 mass%, 0.01 to 0.2 mass%, 0.03 to 0.5 mass%, 0.03 to 0.3 mass%, 0.03 to 0.2 mass%, 0.05 to 0.5 mass%, 0.05 to 0.3 mass%, or 0.05 to 0.2 mass%, based on the total amount of the organic material and the inorganic filler.
[0057] The hindered phenol-based antioxidant may be any compound having a hindered phenol structure. By having a hindered phenol structure, the compound is less likely to decompose (e.g., hydrolyze) even in a high-temperature and high-humidity environment, and the adverse effect of the decomposition on moisture resistance is suppressed.
[0058] Examples of the hindered phenol-based antioxidant include a compound represented by the following formula (2-1), a compound represented by the following formula (2-2), and a compound represented by the following formula (2-3).
[0059] [ka] [ka] [ka]
[0060] In the formula, R 1 represents an alkyl group having 1 to 25 carbon atoms (preferably an alkyl group having 10 to 20 carbon atoms).
[0061] The content of the hindered phenol-based antioxidant in the insulating resin composition may be, for example, 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.15% by mass or more, based on the total amount of the organic material. This makes the above-mentioned effect of the hindered phenol-based antioxidant more pronounced, and tends to further improve the moisture-resistant adhesion and moisture-resistant insulation. The content of the hindered phenol-based antioxidant in the insulating resin composition may be, for example, 10% by mass or less, preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the total amount of the organic material. This tends to further improve the thermal conductivity of the insulating resin composition. That is, the content of the hindered phenol-based antioxidant in the insulating resin composition may be, for example, 0.01 to 10 mass%, 0.01 to 7 mass%, 0.01 to 5 mass%, 0.01 to 4 mass%, 0.05 to 10 mass%, 0.05 to 7 mass%, 0.05 to 5 mass%, 0.05 to 4 mass%, 0.1 to 10 mass%, 0.1 to 7 mass%, 0.1 to 5 mass%, 0.1 to 4 mass%, 0.15 to 10 mass%, 0.15 to 7 mass%, 0.15 to 5 mass%, or 0.15 to 4 mass%, based on the total amount of the organic material.
[0062] The insulating resin composition may further contain other components as organic materials in addition to the above. Examples of other components include surface modifiers such as coupling agents, leveling agents, defoamers, wetting agents, stabilizers, and curing accelerators.
[0063] The inorganic filler is not particularly limited, and any known inorganic filler used for applications requiring insulation and thermal conductivity can be used without particular limitation.
[0064] Examples of the inorganic filler include inorganic fillers composed of aluminum oxide, silica, aluminum nitride, silicon nitride, boron nitride, and the like.
[0065] From the viewpoint of suppressing the decrease in moisture-resistant insulating property caused by hydrolysis of the inorganic material, the inorganic filler is preferably composed mainly of an inorganic material selected from the group consisting of aluminum oxide, silica, silicon nitride, and boron nitride. The content of the inorganic material in the inorganic filler is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the total amount of the inorganic filler.
[0066] For example, when the inorganic filler contains a large amount of aluminum nitride, hydrolysis of the aluminum nitride may occur in a high-temperature and high-humidity environment, resulting in a decrease in insulating properties. Therefore, the content of aluminum nitride in the inorganic filler is preferably 40 mass% or less, more preferably 30 mass% or less, and even more preferably 20 mass% or less, based on the total amount of the inorganic filler. As described above, by using an inorganic material selected from the group consisting of aluminum oxide, silica, silicon nitride, and boron nitride as the main component, the decrease in insulating properties caused by such hydrolysis is significantly suppressed.
[0067] The shape of the inorganic filler is not particularly limited and may be particulate, scaly, polygonal, etc., with particulate being preferred.
[0068] The maximum particle size of the inorganic filler may be, for example, 250 μm or less, preferably 200 μm or less, more preferably 150 μm or less. This tends to further improve the insulating properties of the cured body. The minimum particle size of the inorganic filler is not particularly limited, but from the viewpoint of further improving the thermal conductivity, it may be, for example, 0.05 μm or more, preferably 0.1 μm or more. In this specification, the maximum particle size and the minimum particle size of the inorganic filler refer to the d90 diameter and the d10 diameter in the volume-based particle size distribution, which are measured by a laser diffraction type particle size distribution measuring device.
[0069] The inorganic filler may contain two or more inorganic fillers with different average particle diameters. For example, the inorganic filler may contain a first inorganic filler with an average particle diameter of 25 μm or more and a second inorganic filler with an average particle diameter of 4 μm or less. With such an inorganic filler, the gaps in the first inorganic filler are filled with the second inorganic filler, thereby increasing the packing density and further improving the thermal conductivity of the cured body. In this specification, the average particle diameter of the inorganic filler refers to the d50 diameter in the volumetric particle size distribution. The volumetric particle size distribution is measured using a laser diffraction particle size distribution measuring device.
[0070] The average particle size of the first inorganic filler is preferably 30 μm or more, more preferably 40 μm or more. The average particle size of the first inorganic filler may be, for example, 200 μm or less, preferably 150 μm or less. With such an average particle size, the above-mentioned effects are more pronounced. That is, the average particle size of the first inorganic filler may be, for example, 30 to 200 μm, 30 to 150 μm, 40 to 200 μm, or 40 to 150 μm.
[0071] The average particle size of the second inorganic filler is preferably 3.5 μm or less, more preferably 3 μm or less. The average particle size of the second inorganic filler may be, for example, 0.05 μm or more, preferably 0.1 μm or more. This makes the above-mentioned effects more pronounced. That is, the average particle size of the second inorganic filler may be, for example, 0.05 to 3.5 μm, 0.05 to 3 μm, 0.1 to 3.5 μm, or 0.1 to 3 μm.
[0072] The inorganic filler may further contain a third inorganic filler having an average particle size of more than 4 μm and less than 25 μm. By using such a third inorganic filler, the above-mentioned effects are more pronounced.
[0073] The content of the inorganic filler in the insulating resin composition is 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, based on the total amount of the insulating resin composition. This tends to further improve the moisture-resistant adhesion and thermal conductivity of the cured body. In addition, the content of the inorganic filler in the insulating resin composition is 95% by mass or less, preferably 90% by mass or less, more preferably 85% by mass or less, based on the total amount of the insulating resin composition. This makes it easier to obtain a cured body with improved adhesion and insulation properties in a high-temperature and high-humidity environment, and tends to further improve the heat cycle resistance of the circuit board. That is, the content of the inorganic filler in the insulating resin composition may be, for example, 50 to 95% by mass, 50 to 90% by mass, 50 to 85% by mass, 55 to 95% by mass, 55 to 90% by mass, 55 to 85% by mass, 60 to 95% by mass, 60 to 90% by mass, or 60 to 85% by mass, based on the total amount of the insulating resin composition.
[0074] (Insulating resin hardened body) The insulating resin cured body according to the present embodiment is a cured body of the insulating resin composition described above. The insulating resin cured body can form an insulating layer that has excellent adhesion and insulating properties in a high-temperature and high-humidity environment and a low elastic modulus.
[0075] The storage modulus of the insulating resin cured body at 85° C. is preferably 500 MPa or less, more preferably 400 MPa or less, further preferably 300 MPa or less, and even more preferably 200 MPa or less. By using such an insulating resin cured body, a circuit board having even more excellent heat cycle resistance can be realized.
[0076] The method for producing the insulating resin cured body is not particularly limited. For example, the insulating resin cured body can be produced by heat treating the insulating resin composition to cure it. The heat treatment may be carried out in one step or two steps. By carrying out the heat treatment in two steps, the insulating resin cured body can be formed via a semi-cured body of the insulating resin composition.
[0077] When the heat treatment is carried out in one step, the heat treatment temperature may be, for example, 150 to 250° C., and preferably 160 to 240° C., and the heat treatment time may be, for example, 2 to 15 hours, and preferably 2.5 to 10 hours.
[0078] When the heat treatment is carried out in two stages, the temperature of the first stage heat treatment may be, for example, 60 to 130° C., and preferably 65 to 100° C., and the heat treatment time may be, for example, 0.3 to 8 hours, and preferably 0.5 to 5 hours. The temperature of the second stage heat treatment may be, for example, 150 to 250° C., and preferably 160 to 240° C., and the heat treatment time may be, for example, 2 to 15 hours, and preferably 2.5 to 10 hours.
[0079] By carrying out a heat treatment while maintaining the insulating resin composition or a semi-cured product thereof in a predetermined shape, an insulating resin cured product having a predetermined shape can be obtained. For example, by applying the insulating resin composition onto a metal plate, laminating a metal foil as necessary, and curing the composition, a layered insulating resin cured product can be formed on the metal plate.
[0080] (Laminate) The laminate according to the present embodiment includes a metal plate, a cured insulating resin body disposed on the metal plate, and a metal foil disposed on the cured insulating resin body. In the laminate according to the present embodiment, the metal plate and the metal foil may be separated by the cured insulating resin body, and the cured insulating resin body may function as an insulating layer.
[0081] The metal material constituting the metal plate is not particularly limited, and examples thereof include aluminum, aluminum alloys, copper, copper alloys, iron, stainless steel, etc. The metal plate may be made of one type of metal material, or may be made of two or more types of metal materials. In addition, the metal plate may have a single-layer structure or a multi-layer structure.
[0082] The thickness of the metal plate is not particularly limited, and may be, for example, 0.5 to 3.0 mm from the viewpoint of suitability for producing a circuit board.
[0083] The metal material constituting the metal foil is not particularly limited, and examples thereof include copper, aluminum, nickel, etc. The metal foil may be composed of one type of metal material, or may be composed of two or more types of metal materials. In addition, the metal foil may have a single-layer structure or a multi-layer structure.
[0084] The thickness of the metal foil is not particularly limited, and may be, for example, 5 μm to 1 mm from the viewpoint of suitability for producing a circuit board.
[0085] The thickness of the insulating resin cured body is not particularly limited, and may be, for example, 50 μm to 300 μm from the viewpoint of suitability for producing a circuit board.
[0086] The method for producing the laminate is not particularly limited. For example, the laminate can be produced by a method including a step of applying an insulating resin composition onto a metal plate, curing or semi-curing the composition, and a step of bonding a metal foil onto the cured or semi-cured insulating resin composition (i.e., an insulating resin cured body or semi-cured body). The method may further include a step of curing the semi-cured body of the insulating resin composition. The bonding of the metal foil may be performed by, for example, a roll lamination method, a lamination press method, or the like.
[0087] The laminate can also be produced by a method including a step of applying an insulating resin composition onto a metal foil, curing or semi-curing the composition, and a step of bonding a metal plate onto the cured or semi-cured insulating resin composition (i.e., an insulating resin cured body or semi-cured body). The method may further include a step of curing the semi-cured body of the insulating resin composition.
[0088] Fig. 1 is a cross-sectional view showing a preferred embodiment of a laminate. The laminate 10 shown in Fig. 1 includes a metal plate 1, a metal foil 3, and an insulating layer 2 made of a cured insulating resin interposed between the metal plate 1 and the metal foil 3. By processing the metal foil 3 of the laminate 10 into a predetermined pattern, a circuit board can be easily formed.
[0089] (Circuit board) The circuit board according to the present embodiment includes a metal plate, a cured insulating resin body disposed on the metal plate, and a circuit section disposed on the cured insulating resin body. In the circuit board according to the present embodiment, the metal plate and the circuit section may be separated by the cured insulating resin body, and the cured insulating resin body may function as an insulating layer.
[0090] The metal plate may be, for example, the same as the metal plate in the laminate described above.
[0091] The circuit part may be made of a metal material. Examples of the metal material constituting the circuit part include the same metal material as the metal foil described above. The circuit part may be the metal foil described above processed into a predetermined pattern.
[0092] The thickness of the circuit portion is not particularly limited, and may be, for example, 5 μm to 1 mm from the viewpoints of heat resistance and processability.
[0093] The thickness of the insulating resin cured body is not particularly limited, and may be, for example, 50 μm to 300 μm from the viewpoints of thermal conductivity and insulating properties.
[0094] The circuit board was subjected to a DC voltage of 500 V applied between the circuit and metal plate for 1000 hours in an environment of 85°C and 85% RH. After this, the volume resistivity between the circuit and metal plate at 85°C and 85% RH was 1.0×10 9 It is preferable that the resistance is 5.0×10 Ω·cm or more. 9 It is more preferable that the resistance be Ω·cm or more. Such a circuit board can be said to have particularly excellent moisture-resistant insulation properties.
[0095] The method for producing the circuit board is not particularly limited. For example, the circuit board can be produced by a method including a step of processing the metal foil of the above-mentioned laminate into a predetermined pattern. The method for processing (etching) the metal foil is not particularly limited, and a conventionally known method may be applied.
[0096] Fig. 2 is a cross-sectional view showing a preferred embodiment of a circuit board. The circuit board 20 shown in Fig. 2 includes a metal plate 1, a circuit portion 4, and an insulating layer 2 made of a cured insulating resin interposed between the metal plate 1 and the circuit portion 4. The circuit board 20 may be, for example, a circuit portion 4 formed by processing the metal foil 3 of the laminate 10.
[0097] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES
[0098] <Example 1> (Synthesis of phosphate ester compounds) 90 g of methoxypropanol and 0.3 g of potassium hydroxide were charged into an autoclave, and after replacing with nitrogen, the temperature was raised to 100°C, and 1914 g of propylene oxide was injected over 3 hours while stirring. After that, the mixture was stirred at 90 to 100°C for 30 minutes, cooled, neutralized with phosphoric acid water, dehydrated, and filtered to obtain polypropylene glycol monomethyl ether.
[0099] 400 g of polypropylene glycol monomethyl ether, 100 g of succinic anhydride, and 2 g of tetramethylammonium chloride were charged into an autoclave, and after replacing with nitrogen, the temperature was raised to 100° C., and 58 g of propylene oxide was injected while stirring. After stirring at 100° C. for 2 hours, 558 g of an oily product was obtained.
[0100] 1.8 g of water was added to 558 g of the above oily product, and 14 g of phosphorus pentoxide was added in small portions over about 30 minutes while maintaining the temperature at 50° C. After that, the mixture was stirred at the same temperature for about 1 hour to obtain a phosphate ester compound (P-1) having two hydroxyl groups bonded to the phosphorus atom and having a polyether chain. The number average molecular weight of the obtained phosphate ester was measured by size exclusion chromatography and found to be 510. Tetrahydrofuran was used as the mobile phase, and the measurement was performed with an RI detector (refractometry) at a flow rate of 1.0 ml / min, and the value was calculated in terms of polystyrene. The hydroxyl groups bonded to phosphorus atoms were determined from the results of size exclusion chromatography of the obtained sample and the results of mass spectrometry by LC / MS, 1 H-NMR and 13 This was confirmed by comparing the results of structural analysis using C-NMR.
[0101] (Preparation of insulating resin composition) Bisphenol A / F type epoxy resin (Mitsubishi Chemical Corporation, "YD-6020") 2.2 parts by mass, bisphenol A type hydrogenated epoxy resin (Nippon Steel Sumikin Chemical Co., Ltd., "YX-8000") 6.7 parts by mass, aliphatic amine (Huntsman Corporation, "D-400", amine equivalent 200) 2.4 parts by mass, aliphatic amine (Huntsman Corporation, "D-2000", amine equivalent 1040) 1.6 parts by mass, alumina (DAS45 manufactured by Denka Company, maximum particle diameter 70 μm, average particle diameter 45 μ The mixture was mixed with 30.5 parts by mass of alumina (Denka "DAS10", maximum particle size 21 μm, average particle size 10 μm), 30.5 parts by mass of alumina (Sumitomo Chemical "AA2", maximum particle size 5 μm, average particle size 2 μm), 26.0 parts by mass of alumina (Sumitomo Chemical "AA2", maximum particle size 5 μm, average particle size 2 μm), 0.1 parts by mass of heavy metal deactivator (ADEKA "CDA-6", melting point 212 ° C), 0.1 parts by mass of hindered phenol-based antioxidant 1 (ADEKA "Adeka STAB AO-50"), and 0.2 parts by mass of phosphoric acid ester compound (P-1). The mixture was mixed with a planetary mixer (Thinky "Awatori Rentaro AR-310", rotation speed 2000 rpm) to prepare an insulating resin composition.
[0102] (Circuit board manufacturing) The insulating resin composition was applied onto an aluminum plate having a thickness of 1.5 mm (manufactured by Amano Aluminum Co., Ltd., "A1050 1.5 mm thickness") and dried at 120°C for 15 minutes to bring it into a B-stage (semi-cured) state. The amount of the insulating resin composition applied was adjusted so that the thickness of the insulating layer after curing would be 100 μm.
[0103] Thereafter, a 70 μm thick copper foil (manufactured by Furukawa Electric Co., Ltd., "Electrolytic copper foil, 70 μm thick") was placed on top of the semi-cured body of the insulating resin composition, and the laminated state was heat-treated at 180°C for 6 hours using a heat press method to cure the semi-cured body, thereby obtaining a laminate.
[0104] Next, after masking predetermined positions with an etching resist, the copper foil was etched using a mixed solution of sulfuric acid and hydrogen peroxide as an etching solution. The etching resist was removed, and the substrate was washed and dried to obtain a circuit board having a circuit portion made of copper foil.
[0105] <Example 2> The amount of "DAS45" added was changed to 30.4 parts by mass, the amount of "DAS10" added to 30.4 parts by mass, the amount of "AA2" added to 25.8 parts by mass, and the amount of heavy metal deactivator ("CDA-6") added to 0.4 parts by mass. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0106] <Example 3> The amount of "YX-8000" added was changed to 1.0 part by mass, and the amount of heavy metal deactivator ("CDA-6") added was changed to 0.02 part by mass. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0107] <Example 4> As a heavy metal deactivator, 0.1 parts by mass of "CDA-10" (manufactured by ADEKA, melting point 227°C) was used instead of "CDA-6." Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0108] <Example 5> As a heavy metal deactivator, 0.1 parts by mass of "CDA-1" (manufactured by ADEKA, melting point 320°C) was used instead of "CDA-6." Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0109] <Example 6> An insulating resin composition and a circuit board were obtained in the same manner as in Example 1, except that the amount of the hindered phenol-based antioxidant 1 ("ADK STAB AO-50") added was changed to 0.4 parts by mass.
[0110] <Example 7> An insulating resin composition and a circuit board were obtained in the same manner as in Example 1, except that the amount of the hindered phenol-based antioxidant 1 ("ADK STAB AO-50") added was changed to 0.02 parts by mass.
[0111] <Example 8> As a hindered phenol-based antioxidant, 0.1 parts by mass of "ADEKA STAB AO-60" (manufactured by ADEKA) was used instead of "ADEKA STAB AO-50." Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0112] <Example 9> The amount of "YD-6020" added was changed to 1.3 parts by mass, and the amount of "YX8000" added was changed to 7.6 parts by mass. In addition, as the curing agent, 4.0 parts by mass of a novolac curing agent (manufactured by Meiwa Kasei Co., Ltd., "MEH-8000H") was used instead of the amine curing agent ("D-400" and "D-2000"). Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0113] <Example 10> The amount of "YD-6020" was changed to 6.9 parts by mass, the amount of "YX8000" was changed to 20.7 parts by mass, the amount of "D400" was changed to 7.2 parts by mass, and the amount of "D2000" was changed to 4.8 parts by mass. In addition, instead of alumina ("DAS45", "DAS10" and "AA2"), 60.3 parts by mass of boron nitride ("XGP" manufactured by Denka Co., Ltd., maximum particle diameter 90 μm, average particle diameter 30 μm) was used. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0114] <Example 11> The amount of "YD-6020" was changed to 1.2 parts by mass, the amount of "YX8000" to 3.6 parts by mass, the amount of "D400" to 1.2 parts by mass, the amount of "D2000" to 0.8 parts by mass, the amount of "DAS45" to 32.6 parts by mass, the amount of "DAS10" to 32.6 parts by mass, and the amount of "AA2" to 27.9 parts by mass. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0115] <Comparative Example 1> An insulating resin composition and a circuit board were obtained in the same manner as in Example 1, except that no heavy metal deactivator was added.
[0116] <Comparative Example 2> An insulating resin composition and a circuit board were obtained in the same manner as in Example 1, except that the hindered phenol-based antioxidant was not added.
[0117] <Comparative Example 3> Instead of the hindered phenol-based antioxidant, 0.1 parts by mass of a phosphorus-based antioxidant (ADEKA, "ADEKA STAB 2112") was used. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0118] <Comparative Example 4> Instead of alumina ("DAS45", "DAS10" and "AA2"), 12.0 parts by mass of boron nitride ("XGP" manufactured by Denka Company, maximum particle size 90 μm, average particle size 30 μm) was used. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0119] <Comparative Example 5> The amount of "DAS45" added was changed to 100.0 parts by mass, the amount of "DAS10" added was changed to 100.0 parts by mass, and the amount of "AA2" added was changed to 95.0 parts by mass. Except for the above, an insulating resin composition and a circuit board were obtained in the same manner as in Example 1.
[0120] <Comparative Example 6> An insulating resin composition and a circuit board were obtained in the same manner as in Example 1, except that 0.2 parts by mass of a phosphoric acid ester compound not having a hydroxyl group in the molecule (manufactured by Johoku Chemical Industry Co., Ltd., "JC-224") was added instead of the phosphoric acid ester compound (P-1).
[0121] The formulations of the insulating resin compositions of the Examples and Comparative Examples are shown in Tables 1 and 2. The maximum particle size and average particle size of the inorganic fillers used in the Examples and Comparative Examples were determined by the following method.
[0122] [Measurement of inorganic fillers] Measurements were performed using a Shimadzu SALD-200 laser diffraction particle size distribution analyzer. Specifically, 50cc of pure water and 5g of inorganic filler were added to a glass beaker, stirred with a spatula, and then dispersed in an ultrasonic cleaner for 10 minutes. The inorganic filler dispersion was added drop by drop to the sampler section of the device with a dropper, and the absorbance was allowed to stabilize until it could be measured. Measurements were performed when the absorbance stabilized. In the laser diffraction particle size distribution analyzer, particle size distribution was calculated from the data of the light intensity distribution of diffracted / scattered light by particles detected by the sensor. The maximum particle size was taken as d90, and the average particle size as d50.
[0123] The insulating resin compositions obtained in the Examples and Comparative Examples, and the circuit board obtained in Example 1 were evaluated by the following methods. The results are shown in Tables 1 and 2.
[0124] [Measurement of storage modulus of insulating resin cured body] Measurements were performed using TA Instrument's "RSA-III." Specifically, the insulating resin composition was applied onto a PET film so that the thickness after curing was 200 μm, and cured by heating at 180° C. for 6 hours to produce an insulating resin cured body. The prepared insulating resin cured body was processed to a width of 4 mm and a length of 5 cm to obtain a measurement sample. The obtained sample was used to measure the storage modulus at a measurement frequency of 1 Hz, and heated from -50° C. to 150° C. at a heating rate of 7° C. / min. The storage modulus at 85° C. was calculated from the measurement results.
[0125] [Measurement of thermal conductivity of cured insulating resin] The thermal conductivity was calculated from the thermal diffusivity, specific gravity, and specific heat. Specifically, the thermal conductivity was determined by the laser flash method using a measurement sample made by processing the insulating resin cured body to a width of 10 mm, length of 10 mm, and thickness of 1 mm. The measurement device used was a xenon flash analyzer (NETZSCH LFA447 NanoFlash). The specific gravity was determined by the Archimedes method. The specific heat was determined by using a differential scanning calorimeter (TA Instruments, "Q2000"), which was heated from room temperature to 300°C at a heating rate of 10°C / min in a nitrogen atmosphere.
[0126] [Evaluation of moisture-resistant insulation] For the laminates obtained in the examples and comparative examples, the copper foil was etched to prepare a circular electrode with a diameter of 20 mm, which was used as a measurement sample. Then, a direct current voltage of 500 V was applied between the circular electrode and the metal plate for 1000 hours under the conditions of 85°C and 85% RH. After the voltage application, the volume resistivity between the circular electrode and the metal plate was measured at 85°C and 85% RH for the measurement sample. This measurement was performed using an insulation degradation system (Kusumoto Chemical Industries, Ltd. "SIR13").
[0127] [Evaluation of moisture-resistant adhesion] For the laminates obtained in the examples and comparative examples, the copper foil was etched to prepare a circular electrode with a diameter of 20 mm, which was used as a measurement sample. Next, a direct current voltage of 500 V was applied between the circular electrode and the metal plate for 2000 hours under the condition of 85°C and 85% RH. The case where the electrode part had blistered within 1500 hours from the start of voltage application was evaluated as C, the case where the electrode part had blistered after 1500 to 2000 hours was evaluated as A, and the case where the electrode part had not blistered even after 2000 hours was evaluated as AA. The presence or absence of blistering was visually confirmed.
[0128] [Evaluation of heat cycle resistance] For the laminates obtained in the examples and comparative examples, the copper foil was etched to prepare electrodes, which were used as measurement samples. A chip resistor with a chip size of 2.0 mm x 1.25 mm was soldered between the electrodes of the circuit board, and a heat cycle test was performed 2000 times, with one cycle being -40°C for 15 minutes to +150°C for 15 minutes, in accordance with the JIS-C-0025 temperature change test method. The total number of chip resistors was 20 for each example and comparative example. After the test, the presence or absence of cracks in the soldered parts was observed under a microscope. The cases where the cracks in the soldered parts were 30% or more were evaluated as C, the cases where the cracks in the soldered parts were 10% or more but less than 30% were evaluated as A, and the cases where the cracks in the soldered parts were less than 10% were evaluated as AA.
[0129] [Table 1]
[0130] [Table 2]
[0131] As shown in Tables 1 and 2, it was confirmed that in the examples, an insulating layer having both a low elastic modulus and high thermal conductivity could be formed, and a circuit board having excellent moisture-resistant insulation properties, moisture-resistant adhesion properties, and heat cycle resistance could be obtained. [Industrial Applicability]
[0132] According to the present invention, an insulating layer can be formed that has excellent adhesion and insulating properties in a high-temperature and high-humidity environment and a low elastic modulus. According to the present invention, a circuit board having the insulating layer and excellent moisture-resistant insulation, thermal conductivity, and heat cycle resistance can be obtained. Therefore, the present invention can be suitably used in fields where heat cycle resistance, moisture-resistant insulation, heat dissipation, etc. are required (for example, a circuit board for an on-vehicle filling device, etc.). [Explanation of symbols]
[0133] 1...metal plate, 2...insulating layer, 3...metal foil, 4...circuit portion, 10...laminate, 20...circuit board.
Claims
1. Contains an organic material and an inorganic filler, the organic material contains an epoxy resin, a curing agent, a phosphoric acid ester compound having one or more hydroxyl groups in one molecule, a heavy metal deactivator, and a hindered phenol-based antioxidant; The content of the inorganic material selected from the group consisting of aluminum oxide, silica, silicon nitride, and boron nitride in the inorganic filler is 80 mass% or more based on the total amount of the inorganic filler; The content of the inorganic filler is 50% by mass or more and 95% by mass or less, the content of the phosphate ester compound is 0.05 to 0.4 mass% based on the total amount of the organic material and the inorganic filler, The content of the heavy metal deactivator is 0.01 to 0.5 mass% based on the total amount of the organic material and the inorganic filler, The insulating resin composition has a content of the hindered phenol-based antioxidant of 0.05 to 10 mass % based on the total amount of the organic material.
2. The insulating resin composition according to claim 1 , wherein the curing agent is an amine-based curing agent.
3. The amine-based curing agent is a first amine-based curing agent having an amine equivalent of 300 or less; a second amine-based curing agent having an amine equivalent of 800 or more; The insulating resin composition according to claim 2 , comprising:
4. The insulating resin composition according to any one of claims 1 to 3, wherein the content of the hindered phenol-based antioxidant is 0.05 to 5 mass% based on the total amount of the organic material.
5. The insulating resin composition according to any one of claims 1 to 4, wherein the melting point of the heavy metal deactivator is 250°C or lower.
6. An insulating resin cured product, which is a cured product of the insulating resin composition according to any one of claims 1 to 5.
7. 7. The insulating resin cured product according to claim 6, which has a storage modulus at 85°C of 500 MPa or less.
8. A metal plate; The insulating resin cured body according to claim 6 or 7, which is disposed on the metal plate; A metal foil disposed on the insulating resin cured body; A laminate comprising:
9. A metal plate; The insulating resin cured body according to claim 6 or 7, which is disposed on the metal plate; A circuit portion disposed on the insulating resin cured body; A circuit board comprising:
Citation Information
Patent Citations
COB aluminum-based packaging plate and preparation process thereof
CN110071206A
Metal base board
JP1998242606A
Curable resin composition and metal-base circuit board using the same
JP2002012653A
Epoxy resin composition and flexible printed circuit board material using the same
JP2003026773A
Resin composition for circuit board and metal-based circuit board obtained using the same
JP2004075817A